1996
DOI: 10.3109/00016349609054687
|View full text |Cite
|
Sign up to set email alerts
|

Maternal risk factors for retinopathy of prematurity – a population‐based study

Abstract: Prematurity per se remains the strongest risk factor for ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
0
40
0
4
Order By: Relevance
“…Risk factors for ROP were also studied and a detailed analysis of maternal data from antenatal centres and labour rooms was recently published (Holmströ m et al 1996). An association of ROP with essential hypertension before pregnancy was found.…”
mentioning
confidence: 99%
“…Risk factors for ROP were also studied and a detailed analysis of maternal data from antenatal centres and labour rooms was recently published (Holmströ m et al 1996). An association of ROP with essential hypertension before pregnancy was found.…”
mentioning
confidence: 99%
“…None of the maternal risk factors reported were associated with ROP or its severe form, a finding which is consistent with other studies. 9,12 Our study showed a success rate of 93.7% using cryotherapy, which used to be the standard treatment of retinopathy of prematurity. The current standard is laser treatment, which has been used in different trials with a high success rate, although many centers lack the facilities to use this and so rely on cryotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…Low birth weight is constantly associated with the disease, as, to a lesser extent, is oxygen therapy. 3,5,[11][12][13][15][16][17][18][19][20][21][22]26 Regression of the disease without treatment occurs in the majority of preterm babies who have the disease. However, the threshold stage of ROP is the severe form of the disease, and the recommended treatment is either cryotherapy or laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence varies in different neonatal units (5)(6)(7) and low birth weight has been the only risk factor uniformly identified (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, the disease may occur in the larger birth weight babies but with no information about the prognosis and the risk factors associated with it (10,15).…”
Section: Introductionmentioning
confidence: 99%